DYSTOCIA DUE TO LATERAL DEVIATION OF HEAD AND NECK IN A PRIMIPAROUS MURRAH BUFFALO - KUMAR, SUDHIR; KUMAR, SHARAD; SHARMA, UTSAV; KUSHWAHA, R B; KUMAR, SUDERSHAN; BHARDWAJ, ANAVIL (The Indian Journal of Animal Reproduction, 2023)
Successful caesarean delivery of foetus in dystocia due to lateral deviation of the head and neck in aprimiparous Murrah buffalo has been reported.
Keywords: Dystocia; Caesarean operation; Murrah buffalo